One Diagnosis, Two Perspectives: Lived Experiences of Persons With Young-Onset Dementia and Their Care-Partners. (20th April 2022) - Popok, Paula J; Reichman, Mira; LeFeber, Lisa; Grunberg, Victoria A; Bannon, Sarah M; Vranceanu, Ana-Maria
Abstract: Background and Objectives: Young-onset dementias (YODs) are a set of progressive illnesses that are stressful for both persons with the diagnosis and their care-partners. Although the stressors differ based on their roles and individual experiences, both individuals are at risk for heightened emotional distress (e.g., depression and anxiety). Understanding the unique stressors for each partner and adaptive coping strategies to manage these stressors is important for informing individual and couples-based psychosocial interventions. Research Design and Methods: We conducted open-ended individual interviews with persons with YOD ( N = 12) and their care-partners (i.e., romantic partner; N = 17) over live video. We utilized a hybrid of deductive and inductive analysis techniques to extract individual-level themes and subthemes regarding stressors and adaptive coping strategies. Results: Persons with YOD identified stressors including burden of YOD symptoms, loss of familial roles, resentment toward partner, isolation, and fear of the future. Care-partners identified stressors including managing their partners' symptoms, increased responsibilities, caregiving role, loss of intimacy, social isolation, and grief. For adaptive coping strategies, persons with YOD endorsed use of acceptance, promotion of independence, social support, and engaging in pleasurable activities. Care-partners endorsed value of learning about the diagnosis, using resources, optimism, social support, and self-care. Discussion and Implications: Findings highlight the unique experiences of persons with YOD and their care-partners. Identified themes can be used to inform role-specific psychosocial interventions for both individuals and couples coping with YOD.